Crusading and masculinities
1 online resource.
Keywords: "The purpose of the volume is to further the work of existing studies which have established the importance of gender as a tool of analysis for understanding the Crusades. The book contains essays by established scholars and early career researchers and takes a variety of conceptual and methodological approaches to a range of primary source materials"--